(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
This paper will consider the partial translations of Aeneid, made by Zanzotto (Aen. III 1-72; VI 637-702) and Pasolini (Aen. I 1-301). The aim of this essay is to highlight how the different translation choices, made by the two poets, imply chains of repercussions on the style and the language of Virgilian poem. The analysis of Zanzotto’s translation will reveal a deep adherence to the epic structures of the model, sought within a general tendency to age the original text. On the other hand, the evaluation of Pasolini’s translation will disclose an Aeneid returned by the translator in prosastic forms and in civil tones.